Lamiaceae often used in Portuguese folk medicine as a source of powerful antioxidants: vitamins and phenolics - Barros, Lillian (2010)
Three Lamiaceae often used in Portuguese folk medicine: Ground ivy (Glechoma hederaceae L.), oregano (Origanum vulgare subsp. virens (Hoffmanns. & Link) Ietswaart) and mastic thyme (Thymus mastichina L.), revealed to be good sources of powerful antioxidants such as vitamins (ascorbic acid and tocopherols) and phenolics. The HPLC methodology developed for tocopherols analysis proved to be, after validation assays, sensitive and accurate. Ground ivy showed the highest levels of vitamins: ascorbic acid (168 2 mg/g dry weight) and tocopherols (3692 57 mg/g dry weight). The phenolics extraction was optimized using mastic tyme, and different conditions (water and ethanol:water 50% v/v, 30 min at 25 C and boiling temperature; ethanol and methanol, 24 h at 25 C). The best methodology (25 C, 50 ml of methanol, 24 h) was further applied to the other Lamiaceae. Oregano proved to have the highest radical scavenging and lipid peroxidation inhibition capacity. Particularly, the very low EC50 value (0.01 mg/ml) obtained for TBARS inhibition in brain homogenates is very promising, considering that brain is highly sensitive to oxidative damage. Significantly negative linear correlations were observed between phenolics, including flavonoids, and antioxidant activity EC50 values of the three Lamiaceae.